Are changes in running economy associated with changes in performance in runners? A systematic review and meta-analysis. Issue 13 (3rd July 2019) - O Sullivan, Ian J.; Johnson, Mark I.; Hind, Karen; Breen, Sarah; Francis, Peter
ABSTRACT: Improvements in running economy (RE) are thought to lead to improvements in running performance (P). Multiple interventions have been designed with the aim of improving RE in middle and long-distance runners. The aim of this study was to assess the effect of interventions of at least 2-weeks' duration on RE and P and to determine whether there is a relationship between changes in RE (ΔRE) and changes in running performance (ΔP). A database search was carried out in Web of Science, Scopus and SPORTDiscus. In accordance with a PRISMA checklist 10 studies reporting 12 comparisons between interventions and controls were included in the review. There was no correlation between percentage ΔRE and percentage ΔP (r = 0.46, P = 0.936, 12 comparisons). There was a low risk of reporting bias but an unclear risk of bias for other items. Meta-analyses found no statistically significant differences between interventions and controls for RE (SMD (95% CI) = −0.37 (−1.43, 0.69), 204 participants, p = 0.49) or for P (SMD (95% CI) = −0.65 (−26.02, 24.72, 204 participants, p = 0.99). There is a need for studies of greater statistical power, methodological quality, duration and homogeneity of intervention and population. Standardised measures of performance and greater control over non-intervention training are also required.